A computational review of various inter-facial forces in fully developed multiphase fluid under different flow patterns in vertical column - Faisal Shah; Desheng Zhang; Linlin Geng (Propulsion and Power Research)
The main contribution of this work is a comprehensive overview of the many years of research on various inter-facial forces with distinct flow structure transitions in liquid-gas multiphase flow in vertical columns. Injecting a gas phase into a liquid phase result in a fluid dynamic phenomenology that is substantial, magnetizing, and fascinating. Bubble columns modelling functioning in the bubbly, slug, churn, and annular turbulent flow regime is a major challenge due to their complicated and ephemeral nature. An important modelling choice is how to represent the bubble size distribution. This may be accomplished in several ways, from the relatively simple one of utilizing a single representative bubble size to more intricate techniques. To evaluate the computational findings, we have analysed and discussed several turbulence models in this comparative research. Furthermore, this review summarises the current inter-facial force models, which include turbulent dispersion force, lift force, drag force, wall lubrication force, and virtual mass force. The models of Grace, Tomiyama, Zuber, Antel, Legendre, Burns, and Naumann universal Hosokawa are used, respectively.